2019
DOI: 10.1093/bioinformatics/btz259
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical image augmentation using Augmentor

Abstract: Motivation Image augmentation is a frequently used technique in computer vision and has been seeing increased interest since the popularity of deep learning. Its usefulness is becoming more and more recognized due to deep neural networks requiring larger amounts of data to train, and because in certain fields, such as biomedical imaging, large amounts of labelled data are difficult to come by or expensive to produce. In biomedical imaging, features specific to this domain need to be addressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(104 citation statements)
references
References 0 publications
0
102
0
2
Order By: Relevance
“…Our experiments showed that increasing the dataset up to 30 000 images per category helped to achieve good results. Special care was taken to increase the dataset by using the Augmentor library [49] which permits to rotate images avoiding excessive distortion. Compared to our previous work, the image pre-processing has also been changed: instead of using histogram equalization, CLAHE was selected to enhance the contrast the images.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experiments showed that increasing the dataset up to 30 000 images per category helped to achieve good results. Special care was taken to increase the dataset by using the Augmentor library [49] which permits to rotate images avoiding excessive distortion. Compared to our previous work, the image pre-processing has also been changed: instead of using histogram equalization, CLAHE was selected to enhance the contrast the images.…”
Section: Resultsmentioning
confidence: 99%
“…Because of that, some researchers use right angles. In our case, we have used the Augmentor Library [49], which has been designed to permit rotations of the images limiting the degree of distortion. Additionally, the Augmentor library permits to apply other operations for data augmentation like zoom, bright, shear.…”
Section: Data Augmentation and Dataset Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…operations: Data augmentation resulted in more than 70% duplicate images for each classes, so we needed to generate more than the targeted 600 images. In our experiment, we produced around 2000 images per class using Augmentor (Bloice et al, 2019) (image augmentation library in Python). The data cleaning was done using a MongoDB 2 database to hash the images.…”
Section: Methodsmentioning
confidence: 99%
“…Segmentation annotations are converted to bounding boxes. As for the data augmentation purpose, we apply random rotation, zoom crop/expand, horizontal/vertical flip and distortions by using Augmentor [6]. In the end, we obtain a training set of 25K images.…”
Section: A Data Preparation and Augmentationmentioning
confidence: 99%